2017
DOI: 10.1177/1060028017693029
|View full text |Cite
|
Sign up to set email alerts
|

Pimavanserin: A Novel Antipsychotic for Parkinson’s Disease Psychosis

Abstract: Pimavanserin is a novel 5-HT inverse agonist that has shown promising results for managing hallucinations and delusions in patients with PDP without worsening motor effects or orthostasis. Yet its high cost and specialty pharmacy access may limit use in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Likewise, serotonin has long been implicated in salience attribution (especially aversive salience) and psychosis. 5-HT (serotonin) receptors are targeted by multiple antipsychotics, and the specific 5-HT2A antagonist pimavanserin has recently been approved for the treatment of psychosis in parkinsonian patients ( Bozymski et al, 2017 ; Kianirad and Simuni, 2017 ; Sahli and Tarazi, 2018 ).…”
Section: Limitations and Challenges Of Harnessing The Hippocampus→nacmentioning
confidence: 99%
“…Likewise, serotonin has long been implicated in salience attribution (especially aversive salience) and psychosis. 5-HT (serotonin) receptors are targeted by multiple antipsychotics, and the specific 5-HT2A antagonist pimavanserin has recently been approved for the treatment of psychosis in parkinsonian patients ( Bozymski et al, 2017 ; Kianirad and Simuni, 2017 ; Sahli and Tarazi, 2018 ).…”
Section: Limitations and Challenges Of Harnessing The Hippocampus→nacmentioning
confidence: 99%
“…It is beneficial in psychosis in PD patients with PD, however this effect was not significant for visual hallucinations 8. A large augmentation study in patients with chronic schizophrenia showed improvement on total Positive and Negative Symptom Scale  (PANSS)  score for pimavanserin combined with risperidone, but not for pimavanserin added to haloperidol 9…”
Section: Discussionmentioning
confidence: 99%
“…This observation led to the hypothesis that a serotonin receptor inverse agonist, which binds to the serotonin receptor and decreases its intrinsic activity, may be useful in treating psychosis. Pimavanserin is a novel serotonin receptor inverse agonist that lacks activity at dopamine, muscarinic, adrenergic, and histamine receptors [64], and has recently been approved for PDP, as it reduced hallucinations and delusions in patients with PDP [65].…”
Section: Pimavanserinmentioning
confidence: 99%